2013
DOI: 10.2166/hydro.2013.040
|View full text |Cite
|
Sign up to set email alerts
|

Capacity reliability of water distribution systems

Abstract: Hydraulic power capacity of the water distribution network (WDN) is analyzed, and energetically maximum flows in pipes and networks are determined. The concept of hydraulic power for the analysis of WDN characteristics is presented. Hydraulic power capacity characterizes the WDN capacity to meet pressure and flow demands. A capacity reliability indicator called the surplus power factor is introduced for individual transmission pipes and for distribution networks. The surplus power factor s that characterizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…He [21] proposed a new index, "surplus power entropy", by combining the concept of "flow entropy", proposed by Awumah et al [19], and the index of "surplus power factor" proposed by Vaable [22]. The surplus power entropy is defined as follows:…”
Section: The Basic Theory Of Surplus Power Entropymentioning
confidence: 99%
“…He [21] proposed a new index, "surplus power entropy", by combining the concept of "flow entropy", proposed by Awumah et al [19], and the index of "surplus power factor" proposed by Vaable [22]. The surplus power entropy is defined as follows:…”
Section: The Basic Theory Of Surplus Power Entropymentioning
confidence: 99%
“…The analysis of the surplus power factor revealed that an accurate s value depends on the WDN resistance coefficient C. Therefore, it was crucial to find an approach for determining the C value that will characterize the whole WDN, not just the resistance of individual pipes or the resistance between certain nodes (i.e., the source and the target nodes). The resistance coefficient C is determined in Vaabel et al [4] and for an ordinary city WDN it can be expressed as…”
Section: Development Of Surplus Power Factor Analysismentioning
confidence: 99%
“…The basis for the surplus power factor calculation is the correct determination of the WDN resistance coefficient C. A method for the determination of the C value in WDNs is presented in [4]. This paper describes different approaches applicable to the determination of the surplus power factor and the network resistance coefficient C values.…”
Section: Introductionmentioning
confidence: 99%
“…Vaabel et al. (2008, 2014) and Di Nardo et al. (2017) have developed novel methods to evaluate the availability, robustness, and resilience of WDNs in dynamic scenarios.…”
Section: Introductionmentioning
confidence: 99%